OMBUDSMAN DALAM PERSPEKTIF FIQH SIYASAH: OMBUDSMAN IN FIQH SIYASAH PERSPECTIVE - Ahmad Juninanto; Moch Nurcholis Majid (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
This article contains the Islamic system of government, judicial power (Al-Qada), divided into three regions: Willayat al-Mazalim, Willayat al-Mazalim, and Willayat al-Hisba. Wilayat al-Mazalim is a power in the field of justice which is higher than the power of judges from the power of Muhtasib. This body examines matters that are not within the jurisdiction of ordinary judges. The agency investigates cases of abuse carried out by rulers, judges, or children of powerful people. In this study, the role of institutional control is very important in the study of Siyasah Fiqh. Without supervision, the government will not function. In this regard it has also been shown that the meaning of custodian of the state is found in the Qur'an to refer to a